The Security Paradigm That Strikes a Balance Between a Holistic Security Mechanism and The WSN's Resource Constraints - Umar Danjuma Maiwada; Aminu Aminu Muazu; Nadzira Noor (PT FORMOSA CENDEKIA GLOBAL, 2022)
There is a need for comprehensive holistic security methods that can provide a long-term response to the challenge of security in Wireless Sensor Networks (WSNs). Due to the widespread use of WSN around the world, particularly the Internet of Things (IoTs), quantum security is predicted to aid in the comprehensive security strategy for WSN environments. These quantum securities can be used in conjunction with WSN to provide data security anywhere and at any time. The goal of this study is to examine the security constraints of WSNs and provide a holistic strategy across all network tiers that will serve as a balanced security mechanism solution, as well as a solution to protect nodes from vital data attack, eavesdropping, disruption, destruction as well as alteration and other threats. WSNs are utilized for monitoring, tracking, and controlling applications in a variety of operations, including military, ecological, and health. However, the nature of their resource constraints causes difficulties. Low compute capabilities, tiny memory, limited energy resources, and unreliable communications are just a few of the factors that make data and node security problematic when employing WSN. As a result, as the need for WSNs grows, so does the requirement for improved security methods.